PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN COFFEE SHOP SAN9A GALAXY - Kurnia Gandhy; Arief Syah Safrianto (Jurnal Ekonomi dan Industri, 2020)
This study aims to determine the effect of service quality and price on customer satisfaction at the San9a Galaxy coffee shop. The research method used for data collection is through primary data by distributing questionnaires. The results showed that together it is known that the variables of service quality and price have a positive and significant effect on consumer satisfaction of the San9a Galaxy coffee shop. Based on the partial test, both service quality and price variables have a positive and significant effect on consumer satisfaction of the San9a Galaxy coffee shop consumers.